Nanomaterials - (Wiley-VCH, 2006)
This book surveys the health issues of nanoscale particles and covers the novel aspect of both envieronment protection from as well as with nanpmaterials in depth. Nanomaterials and their toxicity are examined as are their implications for the delicate balance of aqueous systems